Validation of inertial measurement units based on waveform similarity assessment against a photogrammetry system for gait kinematic analysis - Blanco-Coloma, Laura; García-González, Lucía; Sinovas-Alonso, Isabel; Torio-Álvarez, Silvia; Martos-Hernández, Paula; González-Expósito, Sara; Gil-Agudo, Ángel; Herrera-Valenzuela, Diana (Frontiers in Bioengineering and Biotechnology, 2024)
When assessing gait analysis outcomes for clinical use, it is indispensable to use an accurate system ensuring a minimal measurement error. Inertial Measurement Units (IMUs) are a versatile motion capture system to evaluate gait kinematics during out-of-lab activities and technology-assisted rehabilitation therapies. However, IMUs are susceptible to distortions, offset and drifting. Therefore, it is important to have a validated instrumentation and recording protocol to ensure the reliability of the measurements, to differentiate therapy effects from system-induced errors. A protocol was carried out to validate the accuracy of gait kinematic assessment with IMUs based on the similarity of the waveform of concurrent signals captured by this system and by a photogrammetry reference system. A gait database of 32 healthy subjects was registered synchronously with both devices. The validation process involved two steps: 1) a preliminary similarity assessment using the Pearson correlation coefficient, and 2) a similarity assessment in terms of correlation, displacement and gain by estimating the offset between signals, the difference between the registered range of motion (∆ROM), the root mean square error (RMSE) and the interprotocol coefficient of multiple correlation (CMCP). Besides, the CMCP was recomputed after removing the offset between signals (CMCPoff). The correlation was strong (r > 0.75) for both limbs for hip flexion/extension, hip adduction/abduction, knee flexion/extension and ankle dorsal/plantar flexion. These joint movements were studied in the second part of the analysis. The ∆ROM values obtained were smaller than 6º, being negligible relative to the minimally clinically important difference (MCID) estimated for unaffected limbs, and the RMSE values were under 10º. The offset for hips and ankles in the sagittal plane reached -9º and -8º, respectively, whereas hips adduction/abduction and knees flexion/extension were around 1º. According to the CMCP, the kinematic pattern of hip flexion/extension (CMCP > 0.90) and adduction/abduction (CMCP > 0.75), knee flexion/extension (CMCP > 0.95) and ankle dorsi/plantar flexion (CMCP > 0.90) were equivalent when captured by each system synchronously. However, after offset correction, only hip flexion/extension (CMCPoff = 1), hip adduction/abduction (CMCPoff > 0.85) and knee flexion/extension (CMCPoff > 0.95) satisfied the conditions to be considered similar.